A DMS to Support Industrial Process Decision-Making: a contribution under Industry 4.0 - Pereira, Maria Teresa (2020)
This paper presents the development of an Information System (IS) an automotive manufacturing.The system was developed to reduce waste and increase productivity, through better decision-making. The used methodology to implement it was the Business Process Management (BPM). A DMS (Document Management System) for decision making support was built, reducing the action time and providing faster maintenance of all needed data. As a result, the users time decision making and the administrator maintenance was reduced by a total of 26 minutes, corresponding to a 1.61 € reduction per unit built, which means an efficiency of 41%. The present work fits in the company’s strategy for Industry 4.0 and a more sustainable environment, being a positive driver of Industry 4.0 implementation and transformation.